2023
DOI: 10.1108/acmm-02-2023-2755
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of marine organisms on localized corrosion of 316L stainless steel in Dalian seawater

Abstract: Purpose The purpose of this paper is to study the interaction of main marine organisms on localized corrosion of 316L stainless steel in the Dalian Sea area. Design/methodology/approach The steel plate was immersed in the Dalian Sea area for nine months to observe the biofouling and localized corrosion. The local potential distribution on the steel plate covered by marine organisms was measured. The local electrochemical measurements were performed to facilitate understanding the interfacial status under dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The steel plates were immersed about 0.5 m to 2.0 m below the low water line on the test platform to ensure full immersion. More details of the test platform were introduced in a previous study [9]. The test duration was 9 months, from January to October.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steel plates were immersed about 0.5 m to 2.0 m below the low water line on the test platform to ensure full immersion. More details of the test platform were introduced in a previous study [9]. The test duration was 9 months, from January to October.…”
Section: Methodsmentioning
confidence: 99%
“…Crevice corrosion initiated at the edge of the shell base and then resumed inward, proposing that more severe corrosion occurs at barnacle edges due to IR drop. Chen found that the macro-fouling organisms that adhered to 316L stainless steel in the Dalian Sea area are mainly barnacles, ascidians, and mussels [9]. Localized corrosion was observed at both the barnacle edge and center.…”
Section: Introductionmentioning
confidence: 99%